Pregnancy and postpartum period as risk factors for cervical artery dissection - Skrzat, Janusz; Yevstifeieva, Anna; Goncerz, Grzegorz (Folia Medica Cracoviensia, 2026)
Pregnancy and the postpartum period are associated with physiological, hormonal, and hemodynamic changes that may increase susceptibility to cervical artery dissection. Structural alterations of the arterial wall can result from a variety of factors, predisposing vessels to injury and subsequent neurovascular events. In the present study, we analysed the contribution of multiple factors to the development of cervical artery dissection in pregnant women, including advanced maternal age, hormonal status, hypertension, hyperlipidaemia, connective tissue disorders, arterial malformations, migraine, adverse or rapidly changing head and neck positions, neck trauma, chiropractic manipulation, the presence of an elongated styloid process, pressure-inducing activities, and physical exercise.